Molecular Epidemiologic Evaluation of Transmissibility and Virulence of Mycobacterium tuberculosis - Rhee, Jeanne T. (American Society for Microbiology, 1999)
Discovery of genotypic markers associated with increased transmissibility in Mycobacterium tuberculosis would represent an important step in advancing mycobacterial virulence studies. M. tuberculosis strains may be classified into one of three genotypes on the basis of the presence of specific nucleotide substitutions in codon 463 of the katG gene (katG-463) and codon 95 of the gyrA gene (gyrA-95). It has previously been reported that two of these three genotypes are associated with increased IS6110-based clustering, a potential proxy of virulence. We designed a case-control analysis of U.S.-born patients with tuberculosis in San Francisco, Calif., between 1991 and 1997 to investigate associations between katG-463 and gyrA-95 genotypes and epidemiologically determined measures of strain-specific infectivity and pathogenicity and IS6110-based clustering status. We used a new class of molecular probes called molecular beacons to genotype the isolates rapidly. Infectivity was defined as the propensity of isolates to cause tuberculin skin test conversions among named contacts, and pathogenicity was defined as their propensity to cause active disease among named contacts. The molecular beacon assay was a simple and reproducible method for the detection of known single nucleotide polymorphisms in large numbers of clinical M. tuberculosis isolates. The results showed that no genotype of the katG-463- and gyrA-95-based classification system was associated with increased infectivity and pathogenicity or with increased IS6110-based clustering in San Francisco during the study period. We speculate that molecular epidemiologic studies investigating clinically relevant outcomes may contribute to the knowledge of the significance of laboratory-derived virulence factors in the propagation of tuberculosis in human communities.